The HDR book : unlocking the secrets of high dynamic range photography - Concepcion, Rafael (Peachpit Press, 2011)
A guide to HDR offers ten projects, covering a variety of scenarios, with information such topics as tone mapped files, colors, layers, and Camera Raw.